Extreme Learning Machines 2013: Algorithms and Applications - Sun, Fuchen; Toh, Kar-Ann; Romay, Manuel Grana; Mao, Kezhi (Adaptation, Learning, and Optimization, 2014)
In recent years, ELM has emerged as a revolutionary technique of computational intelligence, and has attracted considerable attentions. An extreme learning machine (ELM) is a single layer feed-forward neural network alike learning system, whose connections from the input layer to the hidden layer are randomly generated, while the connections from the hidden layer to the output layer are learned through linear learning methods. The outstanding merits of extreme learning machine (ELM) are its fast learning speed, trivial human intervene and high scalability. Â  This book contains some selected papers from the International Conference on Extreme Learning Machine 2013, which was held in Beijing China, October 15-17, 2013. This conference aims to bring together the researchers and practitioners of extreme learning machine from a variety of fields including artificial intelligence, biomedical engineering and bioinformatics, system modelling and control, and signal and image processing, to promote research and discussions of â_olearning without iterative tuning". This book covers algorithms and applications of ELM. It gives readers a glance of the newest developments of ELM. Â .